A convenient route to internally phosphane-stabilized aryltriborane(7) compounds. Issue 89 (24th October 2018) - Li, Jun; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard
Abstract : The treatment of o -lithiated aryl(dimesityl)phosphanes with excess borane dimethylsulfide adduct eventually gave the aryl substituted internally phosphane-stabilized triborane(7) derivatives. Abstract : The biphenylene derived triborane(7) derivatives7 featuring an internal phosphane donor group can readily be prepared from the respective in situ generated aryllithium compound with excess BH3 ·SMe2 . The internal donor group assisted assembly procedure was also applied to the synthesis of the phenylene bonded triborane(7) compound11 . These aryl-triborane(7) systems can further react with HB(C6 F5 )2 to give the doubly C6 F5 functionalized derivatives12 and13 . The products were characterized spectroscopically and by X-ray diffraction.